Respuesta :

Answer:

[tex] a. = -35 \\ b. = 9a + 1 \\ c. = -35 [/tex]

Step-by-step explanation:

[tex]a. \\ = > \: 7a - 1 + 2a + 2 \\ \\ = > 7( - 4) - 1 + 2( - 4) + 2 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (a = - 4) \\ \\ = > - 28 - 1 - 8 + 2 \\ \\ = > - 37 + 2 \\ \\ = > - 35 \\ \\ \\ b. \\ = > 7a - 1 + 2a + 2 \\ \\ = > 7a + 2a - 1 + 2 \\ \\ = > 9a + 1 \\ \\ \\ c. \\ = > 9a + 1 \\ \\ = > 9( - 4) + 1 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (a = - 4) \\ \\ = > - 36 + 1 \\ \\ = > - 35[/tex]